Histopathological changes in liver, kidney and teratogenic effects of mice on exposure to mosquito repellent - Desy Armalina; Bambang Witjahjo; Neni Susilaningsih (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: Mosquito repellent technology has changed from conventional technology to electric technology, which is more secure and practical. All insect repellent contains chemical compounds that can endanger health. D-Allethrin, the first pyrethroid generation of mosquito repellent is used commercially. Some studies in multi-ethnic population found transplacental transmission in pregnancy. Objective: This study aims to evaluate influences of D-Allethrin in mosquito repellent on liver and kidney, and teratogenic effects in foetal mice. Methods: An experimental laboratory design was conducted in 18 pregnant female Balb/c mice. They were randomized into 3 groups: Group K, P1 and P2. Group K was not given anything. Group P1 and P2 were given exposure pathways of mosquito repellent with inhalation for 12 and 24 hours, in a period of gestational age (0-18 days). On day 19, a Cesar surgery was conducted to take their foetuses and to count the number of living foetuses, dead foetuses, disability, and morphological abnormalities. Results: The administration of allethrin inhalation with dose 12 hours and 24 hours significantly damage mice’s kidney and liver microscopically (p<0.05). A microscopic result of the liver were necrosis in portal areas, hydropic degeneration of lobules, infiltration of inflammatory cells, and fibrosis in the portal area causing a sinusoidal portal to widen. Kidney examination obtained necrosis and hydropic degeneration, as well as the infiltration of lymphocytes and erythrocytes. Teratogenic effects in the foetuses were prematurity and failure of foetal development.Conclusion: Exposure pathways of D-Allethrin in mosquito repellent affected the microscopic appearance of the liver, kidney, and teratogenic effects in the foetuses.